Country Indicators Moderating the Relationship Between Phubbing and Psychological Distress: A Study in 20 Countries - Błachnio, Agata; Przepiórka, Aneta; Gorbaniuk, Oleg; McNeill, Monika; Bendayan, Rebecca; Durak, Mithat; Senol-Durak, Emre; Ben-Ezra, Menachem; Benvenuti, Martina; Angeluci, Alan; Abreu, Ana Maria; Makita, Meiko; et al. (Frontiers in Psychology, 2021)
Problematic mobile phone use can be related to negative mental states. Some studies indicate that behavioural dependency is related to variables associated with the country of origin. The aim of our study was to investigate if country indicators moderated the relationship between phubbing and psychological distress. Our sample consisted of 7,315 individuals from 20 countries, who completed the Phubbing Scale and the Kessler Psychological Distress Scale (K6). The analyses also included country indicators: the Gender Gap Index (GGI), the Human Development Index (HDI), the Social Progress Index (SPI), Hofstede’s dimensions of culture, and the World Happiness Index (WHI). Our results showed that psychological distress was related to at least one dimension of phubbing (i.e., to communication disturbance or phone obsession) in all countries, which means this relationship is culturally universal. The results of the study demonstrate the importance of testing measurement invariance to determine what type of analysis and what type of conclusion are valid in a given study or comparison. Moreover, the increasing or decreasing correlation between phubbing and distress is related to some culture-level indices.